Giant Voc Boost of Low‐Temperature Annealed Cu(In, Ga)Se2 with Sputtered Zn(O, S) Buffers. Issue 9 (13th September 2019) - Zutter, Marco; Virtuoso, Jose; Anacleto, Pedro; Yasin, Liam; Alves, Marina; Madeira, Miguel; Bondarchuk, Oleksandr; Mitra, Saibal; Fuster Signes, David; Garcia, Jorge M.; Briones, Fernando; Waechter, Rolf; et al.
Abstract : An open circuit voltage boost from 0.33 to 0.50 V is reported by M. Zutter et al. (article no.1900145 ) for solar cells comprising industrial‐grade Cu(In, Ga)Se2 absorbers and sputtered Zn(O, S) buffer layers. The research shows that thermal annealing up to 200 °C shifts the dominant recombination pathway from interface to bulk. Concurrently, ultraviolet‐photoelectron spectroscopy reveals an increase of the work function of Zn(O, S) films deposited on Cu(In, Ga)Se2 . The change of conduction band offset and the observed wavelength‐dependent improvement of charge‐carrier collection are consistent with solar cell capacitance simulations. The study identifies future steps needed to achieve efficient cells based on all‐vacuum processed components.